“Away with Passivity!” The Party of Bohemian Conservative Great Landowners at the Beginning of the First World War. (Theatrum historiae, 2007)
At the beginning of the First World War conflicts occurred inside the Party of Bohemian Conservative Great Landowners. They became apparent in the arguments about keynote addresses and newspaper articles. The disunity culminated between 1916 and 1917 as some prominent conservatives decided to leave the election committee. This step prolonged the distance between the two already existing political streams inside the party. One of them, around Friedrich Schwarzenberg, stressed the federalisation programme and sympathised with Czech national parties, whereas the second stream around Heinrich Clam-Martinitz advanced towards German-Austrian centralism. Simultaneously with these trends, the competing aristocratic Party of Constitutional Landowners underwent a process of nationalisation and came close to German national political parties. The new differences of opinion on important issues, e.g. the internal organisation of the monarchy or language questions were caused by various hues of patriotism (covering a wide spectrum from the Reichsdeutsch patriotism to the Bohemian patriotism). In spite of this fact, the landowners constituted a social group in the first place (and political parties in the second place), for which the above mentioned issues represented favourite topics for friendly conversation at common meetings.